Optical studies of a bright Type Iax supernova SN 2020rea. Issue 4 (26th October 2022) - Singh, Mridweeka; Misra, Kuntal; Sahu, Devendra K; Ailawadhi, Bhavya; Dutta, Anirban; Howell, D Andrew; Anupama, G C; Bostroem, K Azalee; Burke, Jamison; Dastidar, Raya; Gangopadhyay, Anjasha; Hiramatsu, Daichi; et al.
ABSTRACT: We present optical photometric and spectroscopic analysis of a Type Iax supernova (SN) 2020rea situated at the brighter luminosity end of Type Iax supernovae (SNe). The light curve decline rate of SN 2020rea is Δ m 15 (g)  = 1.31 ± 0.08 mag which is similar to SNe 2012Z and 2005hk. Modelling the pseudo-bolometric light curve with a radiation diffusion model yields a mass of 56 Ni of 0.13 ± 0.01 M⊙ and an ejecta mass of 0.77$^{+0.11}_{-0.21}$ M⊙ . Spectral features of SN 2020rea during the photospheric phase show good resemblance with SN 2012Z. TARDIS modelling of the early spectra of SN 2020rea reveals a dominance of Iron Group Elements (IGEs). The photospheric velocity of the Si ii line around maximum for SN 2020rea is ∼ 6500 km s −1 which is less than the measured velocity of the Fe ii line and indicates significant mixing. The observed physical properties of SN 2020rea match with the predictions of pure deflagration model of a Chandrasekhar mass C–O white dwarf. The metallicity of the host galaxy around the SN region is 12 + log(O/H)  = 8.56 ± 0.18 dex which is similar to that of SN 2012Z.